The Uses of Copper and Zinc Aluminates to Capture and Convert Carbon dioxide to Syn-gas at Higher Temperature - R. Y. Raskar; A. G. Gaikwad (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
The uses of copper and zinc aluminates to capture and convert the CO2 to syn-gas were studied at higher temperatures. The samples of copper and zinc aluminates were prepared by solid-solid fusion method by calcining in air at 900 oC for 3 h. Those samples were characterized by acidity/alkalinity, surface area, XRD pattern, IR, SEM images and screening to capture CO2 at the different temperatures. The phases Cu2O, CuO, ZnO, CuAl2O4 and ZnAl2O4 were found to be in the samples of zinc and copper aluminates. Acidity and surface area of the samples of copper and zinc aluminates were found to be in the ranges from 0.063 to 9.37 mmol g-1 and 3.04 to 11.8 m2 g-1, respectively. The captured CO2 by the samples of copper and zinc aluminates was found to be 19.92 to 31.52 wt% for the temperature range 40 to 850 oC. The captured CO2 at 550 oC by variable Zn/Al and Cu/Al mol ratio from 0.5 to 6 of the samples of copper and zinc aluminates was found to be 12.81 to 18.04 wt%. The reduction of carbon dioxide by zinc and copper aluminates was observed. The conversion of CO2 by methane over variable mol ratio of Cu/Al and Zn/Al in copper and zinc aluminates, respectively, at 500 oC showed the production of syn-gas by using the gas hourly space velocities (GHSV) 12000, 12000 and 6000 ml. h-1. g-1 of helium, CO2 and methane. The conversions of CO2 by methane over the samples of zinc and copper aluminates were studied at different mol ratios of CO2 to methane. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)